The Evaluation of the History Education Curriculum in Higher Education (History Department, Semarang State University and Historian Society of Indonesia, 2022)
This study aims to: (1) find out the relevance of the history study program curriculum to the field needs, (2) find out the advantages of the current program curriculum, and 3) find out what content needs to be strengthened in the curriculum program in Indonesia. This research method uses mixed approaches. While the strategy used is that the research has been planned in detail in the proposal before the researcher goes into the field, the suitable strategy is embedded research. The results of the study are: (1) the relevance shows that overall the curriculum content of the program is included in the excellent category or has a good weight; aspects of curriculum implementation amounting to 4.09 which shows that the implementation of the curriculum is already proper, and aspects of curriculum relevant to the needs of the field in the very good category; (2) the advantages of the curriculum that the curriculum has competitive advantages that generally involve; and (3) the things that need to be strengthened include several things such as (1) the need to balance the weight and content of courses, (2) the need for expansion of practicum subjects and the provision of tools, (3) the necessity of conducting prerequisite courses, and (4) the pattern thesis guidance which is further intensified. Penelitian ini bertujuan untuk: (1) mengetahui relevansi kurikulum prodi sejarah dengan kebutuhan lapangan, (2) mengetahui kelebihan kurikulum prodi yang ada, dan 3) mengetahui konten apa yang perlu diperkuat dalam program kurikulum di Indonesia. Metode penelitian ini menggunakan pendekatan campuran. Sedangkan strategi yang digunakan adalah penelitian yang telah direncanakan secara rinci dalam proposal sebelum peneliti terjun ke lapangan, strategi yang cocok adalah penelitian tertanam. Hasil penelitian adalah: (1) relevansi menunjukkan bahwa secara keseluruhan isi kurikulum program studi termasuk dalam kategori sangat baik atau memiliki bobot yang baik; aspek implementasi kurikulum sebesar 4,09 yang menunjukkan bahwa implementasi kurikulum sudah tepat, dan aspek kurikulum relevan dengan kebutuhan lapangan dalam kategori sangat baik; (2) keunggulan kurikulum bahwa kurikulum memiliki keunggulan kompetitif yang umumnya menyangkut; dan (3) hal-hal yang perlu diperkuat meliputi beberapa hal seperti (1) perlunya keseimbangan bobot dan isi mata kuliah, (2) perlunya perluasan mata kuliah praktikum dan penyediaan alat, (3) perlunya penyelenggaraan mata kuliah prasyarat, dan (4) pola bimbingan skripsi yang semakin diintensifkan. Cite this article: Setiawan, R., Aman. (2022). The Evaluation of the History Education Curriculum in Higher Education. Paramita: Historical Studies Journal, 32(2), 263-275. http://dx.doi.org/10.15294/paramita.v32i2.34535